The level of information technology adoption and its factors in micro, small, and medium enterprises in Jambi City, Indonesia - Amril Amril; Layra Nichi Sari (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
This study aims to analyze the conditions and the level of information technology (IT) adoption in micro, small, and medium enterprises (MSMEs) in Jambi City and its factors. The data was obtained by carrying out a sample survey on MSMEs in Jambi City. The study uses descriptive analysis and Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of the study found that: 1) the level of IT adoption in MSMEs in Jambi City is still relatively low. About one third of MSMEs is still using IT only for internally oriented functional integration. On the contrary, only 1.89 percent of MSMEs have been in the stage of business scope redefinition under influence of IT; 2) Behavior intention has a significant effect on the level of IT adoption in MSMEs. Furthermore, there are five variables that influence behavioral intention of MSMEs related to the use of IT. Those are effort expectance, social influence, hedonic motivation, price value, and habit.